2017
DOI: 10.1016/j.neuroscience.2016.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Rodent models of obsessive compulsive disorder: Evaluating validity to interpret emerging neurobiology

Abstract: Obsessive Compulsive Disorder (OCD) is a common neuropsychiatric disorder with unknown molecular underpinnings. Identification of genetic and non-genetic risk factors has largely been elusive, primarily because of a lack of power. In contrast, neuroimaging has consistently implicated the cortico-striatal-thalamo-cortical (CSTC) circuits in OCD. Pharmacological treatment studies also show specificity, with consistent response of OCD symptoms to chronic treatment with serotonin reuptake inhibitors; although most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(31 citation statements)
references
References 171 publications
(230 reference statements)
0
24
1
6
Order By: Relevance
“…The glutamatergic hypothesis of OCD has accumulated support over the last decades [4,5]. Neuroimaging studies indicate alterations in the cortical-striatal-thalamic-cortical (CSTC) circuitry, which includes glutamatergic corticostriatal projections synapsing onto striatal spiny projection neurons and/or interneurons [4,[6][7][8][9][10]. Altered glutamate levels from cerebrospinal fluid studies have been reported in OCD [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The glutamatergic hypothesis of OCD has accumulated support over the last decades [4,5]. Neuroimaging studies indicate alterations in the cortical-striatal-thalamic-cortical (CSTC) circuitry, which includes glutamatergic corticostriatal projections synapsing onto striatal spiny projection neurons and/or interneurons [4,[6][7][8][9][10]. Altered glutamate levels from cerebrospinal fluid studies have been reported in OCD [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Beneficial effects of anti-glutamatergic agents including memantine, N-acetylcysteine, riluzole, ketamine, and rapastinel have been reported in treatment-resistant OCD individuals [5,[13][14][15][16][17]. In addition, some genetic animal models with altered glutamatergic neurotransmission at the CSTC circuitry exhibit OCD relevant behaviors [10,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Наличие при парафилиях навязчивых аномальных сексуальных фантазий и компульсивных их реализаций приближает расстройства сексуального предпочтения по своей психопатологической структуре к обсессивно-компульсивным расстройствам (ОКР). Необходимо также отметить, что связь между дисфункцией серотонинергической системы и обсессивными расстройствами достаточно давно обсуждается в литературе, и в 2017 г. был опубликован обзор литературы, в котором на этом основании предлагались различные патогенетические модели ОКР [14]. В более ранних исследованиях [15] также предполагалось наличие дисфункции серотониновых 5-НТ-рецепторов с патогенезом ОКР.…”
Section: Discussionunclassified
“…Кроме того, дисфункция ПФК у лиц с ОКР была выявлена и при применении позитронной эмиссионной томографии [19]. По имеющимся в литературе данным, в патогенез ОКР могут быть вовлечены и другие, в частности эмоциогенные и мотивационные, структуры -островок, миндалина [14].…”
Section: Discussionunclassified
“…Onychophagia (nail biting), trichotillomania (hair pulling), cutting and picking, repetitive piercing and tattooing, excessive use of cosmetic procedures, are common observations in clinical practice (Figures 1 and 2). [13][14][15][16][17] Repeated behaviors that involve the skin, especially those that leave marks or are accompanied by specimens, can be seen, graded and noted in the chart. In laboratory settings, neuroscientists have created maps of brain function and circuitry in task and non-task related situations.…”
Section: Introductionmentioning
confidence: 99%